THE ROAD TO RECONCILIATION: GOVERNMENT STRATEGIES AND AMERICAN MUSLIM INCLUSION SINCE 9/11 - Alsharari, Abdullah Mohammed; Alsharari, Abdullah Saleh (Ayden International Journal of Law, Political Science, and Administration, 2024)
American Muslim communities are diverse, growing, and play an increasingly significant role in the United States. Estimating their numbers is challenging due to limitations on gathering religious affiliation data by government agencies. However, estimates suggest a population of two to seven million American Muslims, constituting a minority but still significant percentage of the total population. This demographic diversity underscores the importance of understanding the experiences and needs of American Muslims as an integral part of the nation's social fabric.